RT-office for optimization of industrial EB and X-ray processing - Lazurik, V.T.; Lazurik, V.M.; Popov, G.F.; Rogov, Yu.V. (Вопросы атомной науки и техники, 2004)
The conception for design of the Radiation-Technological Office (RT-Office) was developed by authors. RTOffice realize computer technologies at all basic stages of works execution on the radiation-technological lines (RTL) using irradiators of electron beam (EB), X-ray and γ-ray. The description of the programs ModeRTL and XRSoft which are intended for simulation of EB and X-ray processing is considered in the paper.